To capture the child’s interest - nurses experiences of ‘Saga stories in health talks’ - Camilla Collan; Lina Dahl; Maria Henström; Christine Delisle Nyström; Marie Löf; Susanne Andermo (BMC Nursing, 2024)
Abstract Background As unhealthy lifestyle habits have been found to be established early in life and often track into adulthood, early preventive initiatives are important. ‘Saga Stories in health talks’ is a newly developed material that is intended to be used as a support for nurses at child health care (CHC) centers in their health talks with children and parents in Sweden. The aim of this study is to explore how CHC nurses experience the usability of the ‘Saga Stories in health talks’ material. Methods This study used a qualitative design. The material ‘Saga Stories in health talks’ was tested by 33 CHC nurses working in 11 CHC centers in three regions in Sweden. All CHC nurses were invited to participate in the interviews and 17 agreed. The interviews were transcribed and analysed using content analysis. Results Three categories and eight sub-categories emerged. The categories were: (1) An appreciated tool suitable for health talks, (2) Illustrations to capture children’s interest in the conversation with families, and (3) Barriers and facilitators. Saga Stories in health talks’ was experienced by the CHC nurses as an appreciated tool with content highly relevant to what should be discussed during the health talks. The CHC nurses described the material as well-designed with illustrations that helped them capture the child’s interest and increase their participation, while still involving the parents. Support from colleagues, the researchers, and managers were seen as important facilitators. Challenges included structural factors such as how and when to best use the material, especially concerning that the 4-year visit contained many other mandatory parts. Conclusions This pilot study show that the material ‘Saga Stories in health talks’ was highly appreciated by CHC nurses and facilitated their health talks with families in CHC. Important aspects with the material were the relevant content and the focus on healthy living habits, as well as the child friendly illustrations. These findings can be used when similar material is developed to facilitate health talks with families in other contexts. Our results also highlight the importance to adjust the implementation of a new material with already established practice and routines.